Table of Content - - (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content: 1. Mohamed ‘Ali Al-Tajer and His Book ‘Aqd al-La’al fi Tarikh Awal: A Critical reading of its content in the history of Bahrain Co-Prof. Khalid Ismail Nayif Al-Hamadani 2. The ideal theory in Plato’s Philosophy and it’s relevance to man and the universe Mrs. Nadha Mutlaq ALbogami 3. Reality and challenges of the work environment of Agricultural Engineers working in the private and non-governmental sectors in the West Bank, Palestine considering some variables Mr. Salem Nassr, Mrs. Doaa Zayed 4. The motives of the Sudanese citizen’s use of YouTube and the gratifications achieved from it sample of citizens of Khartoum State for the year 2023 Co-Prof. Badereldin Ali Hamed Mohammed 5. An analysis of political speeches on racism by President Donald Trump during his presidency Mrs. Brooj Nasser A. Alsaqer 6. Images of Arabs and Islam in Burton’s Pilgrimage to Al-Madinah and Meccah Mr. Abdulkarim Mohammad Alseadoon, Dr. Geoffrey Nash 7. The Translation of Yemeni – Arabic legal documents into English: Problems and Suggestions Mrs. Hakima Mansour Ahmed Khoshafah